2023
DOI: 10.7150/ijms.77206
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Impact of Pharmacogenetics and Metabolomics on the Efficacy of Metformin in Type 2 Diabetes

Abstract: Metformin is the most often prescribed drug for people with type 2 diabetes (T2D). More than 120 million patients with T2D use metformin worldwide. However, monotherapy fails to achieve glycemic control in a third of the treated patients. Genetics contribute to some of the inter-individual variations in glycemic response to metformin. Numerous pharmacogenetic studies have demonstrated that variations in genes related to pharmacokinetics and pharmacodynamics of metformin's encoding transporters are mainly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 84 publications
0
18
0
1
Order By: Relevance
“…For patients with DM2, metformin is the most often recommended medication. Metformin is used by more than 120 million type 2 diabetes patients globally [ 26 ]. However, individual differences in the pharmacological response to metformin are significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For patients with DM2, metformin is the most often recommended medication. Metformin is used by more than 120 million type 2 diabetes patients globally [ 26 ]. However, individual differences in the pharmacological response to metformin are significant.…”
Section: Discussionmentioning
confidence: 99%
“…Some interindividual variations in the glycaemic response to metformin are influenced by genetics. Numerous pharmacogenetic investigations have shown that differences in the genes that encode the transporters responsible for the pharmacokinetics and pharmacodynamics of metformin are often related to metformin response [ 26 ]. Metformin’s total exposure and efficacy can be increased or decreased by certain genetic polymorphisms; hence, these variations must be examined to get the optimal therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Рекомендації такого федерального американського консультативного комітету, як Національна комісія з клінічної допомоги (National Clinical Care Co��ission), передбачають широке застосування метформіну в осіб з переддіабетом з метою попередження розвитку ЦД [9]. Такі наполегливі рекомендації зумовили те, що зараз в усьому світі метформін приймають >120 млн хворих на ЦД [10].…”
Section: вступunclassified
“…8 Metformin has been used for several decades as the first-line therapy for T2D in the United States. However, only a few studies 9 have performed metabolomic analyses on metformin-treated patients. Moreover, although visceral fat accumulation is associated with insulin resistance and various metabolic complications, 10 no metabolomic studies evaluating visceral fat content reduction by SGLT2 inhibitors have been reported.…”
Section: Introductionmentioning
confidence: 99%